C1q/TNF-α–Related Protein 1 (CTRP1) Maintains Blood Pressure Under Dehydration Conditions - Han, Sora; Jeong, Ae Lee; Lee, Sunyi; Park, Jeong Su; Buyanravjikh, Sumiyasuren; Kang, Wonku; Choi, Seungmok; Park, Changmin; Han, Jin; Son, Woo-Chan; Yoo, Kyung Hyun; Cheong, Jae Hoon; et al. (Circulation research, 2018)
RATIONALE:Circulating C1q/TNF-α-related protein 1 (CTRP1) levels are increased in hypertensive patients compared to in healthy subjects. Nonetheless, little is known about the molecular and physiological function of CTRP1 in blood pressure (BP) regulation. OBJECTIVE:To investigate the physiological/pathophysiological role of CTRP1 in BP regulation. METHODS AND RESULTS:CTRP1 production was increased to maintain normotension under dehydration conditions, and this function was impaired in inducible CTRP1 knockout mice (CTRP1). The increase in CTRP1 under dehydration conditions was mediated by glucocorticoids, and the antagonist mifepristone prevented the increase in CTRP1 and attenuated BP recovery. Treatment with a synthetic glucocorticoid increased the transcription, translation, and secretion of CTRP1 from skeletal muscle cells. Functionally, CTRP1 increases BP through the stimulation of the angiotensin II receptor 1 (AT1R)-Ras homolog gene family (Rho)/Rho kinase (ROCK) signaling pathway to induce vasoconstriction. CTRP1 promoted AT1R plasma membrane trafficking through phosphorylation of AKT and AKT substrate of 160 kDa (AS160). In addition, the administration of an AT1R blocker, losartan, recovered the hypertensive phenotype of CTRP1 transgenic (TG) mice. CONCLUSIONS:For the first time, we provide evidence that CTRP1 contributes to the regulation of BP homeostasis by preventing dehydration-induced hypotension.